PENGARUH PELAKSANAAN PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP EFEKTIVITAS KERJA PEGAWAI KANTOR UNIT PELAYANAN TERPADU VI DINAS PENDAPATAN DAERAH KOTA MEDAN - Ovi Aldino Akbar Nasution (PERSPEKTIF, 2016)
The formulation of the problem in this research is "How to influence the implementation of the principles of Good Governance Effectiveness Against Employee Work Integrated Service Unit VI office of the Regional Revenue Office Terrain". This research was conducted at the office of the Integrated Service Unit VI Regional Revenue Office staff Medan.Populasi study were all employees of the Office of Integrated Services Unit VI Regional Revenue Office Medan. Sample set as many as 51 people consisting of staff and honorary Office of Integrated Services Unit VI Regional Revenue Office Medan.Mechanical Analysis of the data is carried out by quantitative descriptive analysis, and the relationship between the variables used untukmengetahui Correlation analysis Product MomentPearson. The results of this study is that the implementation of the principles GoodGovernance in the Office of Integrated Services Unit VI Regional Revenue Office Medan categorized either